2022
DOI: 10.3389/fonc.2022.1021615
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral glucose changes after chemotherapy and their relation to long-term cognitive complaints and fatigue

Abstract: PurposeTo investigate the short-term cerebral metabolic effects of intravenous chemotherapy and their association with long-term fatigue/cognitive complaints.Experimental designUsing [18F]-FDG-PET/CT whole-body scans, we retrospectively quantified relative cerebral glucose metabolism before and after neoadjuvant chemotherapy in a cohort of patients treated for non-metastatic breast cancer (2009-2019). Self-report of cognitive complaints and fatigue were prospectively assessed 7 ± 3 years after therapy. Metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
(86 reference statements)
2
0
0
Order By: Relevance
“…First, the hypometabolism in the right limbic areas was not observed in subjects who underwent a post-chemotherapy PET analysis, suggesting that systemic chemotherapy can directly or indirectly alter brain metabolism through the interaction with the breast neoplasm. This result is in accordance with recent reports on a large cohort of non-metastatic BC patients after NAC [ 54 ]. Schroyen et al [ 54 ] observed both hyper- and hypometabolism in different brain regions depending on the administered regimen of chemotherapy for BC, even in the absence of any overt neurological symptoms, such as cognitive impairments.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…First, the hypometabolism in the right limbic areas was not observed in subjects who underwent a post-chemotherapy PET analysis, suggesting that systemic chemotherapy can directly or indirectly alter brain metabolism through the interaction with the breast neoplasm. This result is in accordance with recent reports on a large cohort of non-metastatic BC patients after NAC [ 54 ]. Schroyen et al [ 54 ] observed both hyper- and hypometabolism in different brain regions depending on the administered regimen of chemotherapy for BC, even in the absence of any overt neurological symptoms, such as cognitive impairments.…”
Section: Discussionsupporting
confidence: 94%
“…This result is in accordance with recent reports on a large cohort of non-metastatic BC patients after NAC [ 54 ]. Schroyen et al [ 54 ] observed both hyper- and hypometabolism in different brain regions depending on the administered regimen of chemotherapy for BC, even in the absence of any overt neurological symptoms, such as cognitive impairments. Second, the baseline PET pattern in the right insular regions appeared to be correlated to BC activity.…”
Section: Discussionsupporting
confidence: 94%